The resting metabolic values related to different sport disciplines - Nestorova, Mihaela; Spirkoska Vangelovska, Biljana; Dejanova, Beti; Karagjozova, Ivanka; Pluncevikj Gligoroska, Jasmina (Faculty of Physical Education, Sport and Health, Skopje, Republic of Macedonia, 2022)
Abstract Athletes compared to physically inactive people have a higher percentage of muscle mass which is a result of their active lifestyle. Higher percentage of muscle mass contributes to higher value of resting metabolic rate (RMR) in athletes. The aim of this study is to compare the values of resting metabolic rate in different sports disciplines which will give us a general knowledge of the energy expenditure in different sports. A number of 79 male athletes from 4 different sports (handball, football, cycling and functional fitness) were included in this study. Bioelectrical analisator In Body 720, Great Britain was used for body composition analysis and indirect calorimeter Fit Mate, COSMED, (Italy) for resting metabolic rate. All participants completed questionnaires for their medical history and physical activity. The results showed that handball players have significantly higher values of height, weight and skeletal muscle mass compared to the other sports (p<0,05), while percentage of body fat was lowest among football players. Handball players have higher values for RMR compared to the other sports, but have statistically different values only compared to cyclists. Cyclists have significantly lower values for RMR compared to the other sports (p<0,05). Because RMR has a major impact on total daily energy expenditure (TDEE) we come to the conclusion that handball players have higher TDEE and they need a balanced nutritional regimen that will provide all required nutrients, preferably with a higher caloric rate. Key words: athletes; resting metabolic rate; energy expenditure
Keywords: athletes; resting metabolic rate; energy expenditure